"Tupi or not Tupi" versus "Casa Portuguesa": Friction between Lúcio Costa and Raul Lino in Auriverde Jornada (or the debate that might have taken place on Identity and Heritage in Architecture) - Santos, Joaquim Rodrigues dos (2022)
In the book Auriverde Jornada, Raul Lino recounts his meeting with Lúcio Costa in Rio de Janeiro in 1935. That brief shared moment, their personal convictions in relation to architecture and the affinities and divergences that unite/distance them serve as the point of departure for a comparative analysis of their professional journey in the sphere of heritage safeguarding. In fact, as well as landmarks in the architectural landscape of their respective countries, Lino and Costa were also towering figures in the heritage pathway, taking different directions but also sometimes moving in parallel. The animated debate between Lino and Costa on the spirit of modern architecture functions as a catalyst for the present essay, which encompasses a wider problematic: the construction of identity in architecture, the idiosyncrasies of the Modern Movement and the patrimonialization of architecture in Portugal and Brazil, as well as the relations, influences and repercussions that existed in this area between both countries between 1930 and 1960.